Highly Filled Papers, on their Manufacturing, Processing, and Applications. Issue 6 (29th May 2019) - Dermeik, Benjamin; Lorenz, Hannes; Bonet, Alexander; Travitzky, Nahum
Abstract : Since more than a decade ago, the research on highly filled papers, as well as paper‐derived inorganic materials, has greatly intensified. As presented in this review, highly filled papers as preforms allow for the design of porous or dense, multilayered, and geometrically complex structures. These paper‐derived ceramic‐ or metal‐based materials are generated by the heat‐treatment of highly filled papers. Paper‐derived materials are potential materials of choice for applications in transportation, energy‐generation, environmental conservation, support structures, medical uses, and electronic components. Due to the adjustability of the filler content and the good machinability of highly filled papers, paper‐derived sheets or multilayers may include intricate structures and tailored gradients in phase structure or porosity. Paper‐derived multilayers also may contain cast ceramic tapes or other functionalized layers, as presented in some examples. Computer‐aided manufacturing processes for paper‐derived materials can be supplemented by prediction models for the sintering shrinkage in order to identify optimal post‐processing steps, stacking orders and orientations for highly filled paper layers within multilayer green bodies. The accuracy of established component‐level sintering models can be significantly increased by microstructure models of the highly filled paper. Abstract : Papers, highly filled with metals or ceramics, can be easily machined and can be combined into geometrically complex or multilayered structures. Porous or dense, homogenous or functionally graded inorganic materials are achieved by the heat treatment of highly filled papers. The computer‐aided manufacturing of paper‐derived materials, including sintering shrinkage models, can present an economical method for generating near‐net‐shaped ceramic‐ or metal‐based composites which are adaptable to a wide range of technical applications. Adapted with permissions. 18, 42, 156 © 2008 Wiley, © 2018 Elsevier, ©2010 HvB Verlag GbR.